(untitled) (Research, Society and Development, 2021)
Introduction: Dentoalveolar injuries (ADD) can be defined as injuries that are caused by impacts on teeth and / or hard and soft tissues inside and / or outside the oral cavity. Objective: To perform a literature review literature review about dentoalveolar injuries. In general, the main epidemiological indices, etiology, forms of diagnosis and classification of dentoalveolar injuries will be addressed. Methods: A bibliographic search was performed in the PubMed database, filtering publications from the last 10 years. The search was performed with previously selected descriptors. The research took place in 3 phases and the articles were included according to the inclusion and exclusion criteria. Results: ADD injuries can affect children, adolescents and adults, but are quite common during childhood. Prevalence data vary and the most frequent causes are falls, sports accidents (cycling), traffic accidents and physical violence. The conduct performed in these cases directly interferes with the treatment results, so it is important that the dentist has adequate knowledge on how to act in front of these injuries. Conclusion: Dentoalveolar injuries are injuries routinely seen in clinical dental practice. Making a proper diagnosis is essential for effective treatment and for the patient to have the best possible prognosis.